2020
DOI: 10.3389/fmed.2020.00106
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Body Composition Analysis and Malnutrition Risk Questionnaire in the Assessment of Nutritional Status of Patients With Initially Diagnosed Crohn's Disease

Abstract: Objective: This study was carried out to investigate the role and necessity of human body composition analysis in assessing the nutritional status of initially diagnosed Crohn's disease (CD) patients.Methods: A total of 47 initially diagnosed CD patients were recruited. The skeletal muscle mass index (SMI), fat-free mass index (FFMI), body fat mass, body fat percent, visceral fat area (VFA), and body cell mass were determined with the Biospace Inbody S10 composition analyzer.Results: In 47 patients with initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…The active inflammation will also cause protein loss, which will further reduce the concentration of serum albumin, thus increasing nutritional risk. The levels of PLT, HB, HCT, and ALB were also independent risk factors affecting the nutritional status of children with CD [ 16 ]. The count changes of serological PLT, HB, HCT, and ALB count have been proved to be used as nutritional evaluation indexes in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The active inflammation will also cause protein loss, which will further reduce the concentration of serum albumin, thus increasing nutritional risk. The levels of PLT, HB, HCT, and ALB were also independent risk factors affecting the nutritional status of children with CD [ 16 ]. The count changes of serological PLT, HB, HCT, and ALB count have been proved to be used as nutritional evaluation indexes in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jingyong Xu showed that nutritional support therapy after the GLIM assessment removed muscle mass and neglected the benefits of reducing infection complications ( 13 ). In our previous research, we also found that some IBD patients with muscle mass reduction cannot be identified by commonly used nutrition assessment scales such as NRS-2002 ( 21 ). Our team has considered whether GLIM-China has an impact on malnutrition diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nutritional status assessment of these patients becomes much more important. Currently, the main nutritional assessment tools or parameters are used including body mass index (BMI), Nutritional Risk Screening-2002(NRS-2002, and Patient-Generated Subjective Global Assessment (PG-SGA) (4)(5)(6)(7)(8). The Asian diet and inflammatory bowel disease (IBD) working group emphasized that weight or BMI alone cannot accurately predict the nutritional status of the patient (4); unfortunately, they did not also clearly indicate the appropriate nutrition assessment method for IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the second step of GLIM can not be continued once NRS-2002 shows no nutritional risk. Our previous study found that patients with a negative NRS-2002 result may also had a low muscle mass ( 6 ), suggesting that some patients may have nutritional risk or even malnutrition that can not be screened out by NRS-2002 ( 10 ). Should other validated tools be used for the first step of GLIM criteria as nutritional risk screening?…”
Section: Introductionmentioning
confidence: 99%